Attitude toward oral biopsy among general dental practitioners: Awareness and practice - Anwar B Bataineh; Huda M Hammad; Iyas A Darweesh (Wolters Kluwer Medknow Publications, 2015)
Aims: The aim of this study was to investigate the theoretical and practical skill levels of the general dental practitioners (GDPs) toward oral biopsy and to compare these results with other developed countries. Materials and Methods: A total of 500 Jordanian GDP from the 12 major governances of the Hashemite Kingdom of Jordan were conveniently sampled and included in this cross-sectional study. Participants were asked to complete a self-reported questionnaire that was specially designed to achieve the aims and objectives of this study. Results: Results demonstrated that a significant difference exists between the perceived theoretical knowledge related to oral biopsy and the clinical practical application of this knowledge among the participant dentists. Although 93.8% of the participants claim to have the ability to diagnose oral mucosal lesions, 91.4% recognize the diagnostic importance of oral biopsy and 67% know the indications of performing an oral biopsy, only 30.7% consider the oral biopsy as a diagnostic method to be used to reach a diagnosis of an oral mucosal lesion. Conclusions: A significant difference present between the theoretical information related to oral biopsy and the practical application of this information among the GDP.